PGC-1α-mediated changes in phospholipid profiles of exercise-trained skeletal muscle - Senoo, Nanami (J Lipid Res, 2015)
Exercise training influences phospholipid fatty acid composition in skeletal muscle and these changes are associated with physiological phenotypes; however, the molecular mechanism of this influence on compositional changes is poorly understood. Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), a nuclear receptor coactivator, promotes mitochondrial biogenesis, the fiber-type switch to oxidative fibers, and angiogenesis in skeletal muscle. Because exercise training induces these adaptations, together with increased PGC-1α, PGC-1α may contribute to the exercise-mediated change in phospholipid fatty acid composition. To determine the role of PGC-1α, we performed lipidomic analyses of skeletal muscle from genetically modified mice that overexpress PGC-1α in skeletal muscle or that carry KO alleles of PGC-1α. We found that PGC-1α affected lipid profiles in skeletal muscle and increased several phospholipid species in glycolytic muscle, namely phosphatidylcholine (PC) (18:0/22:6) and phosphatidylethanolamine (PE) (18:0/22:6). We also found that exercise training increased PC (18:0/22:6) and PE (18:0/22:6) in glycolytic muscle and that PGC-1α was required for these alterations. Because phospholipid fatty acid composition influences cell permeability and receptor stability at the cell membrane, these phospholipids may contribute to exercise training-mediated functional changes in the skeletal muscle.